2009
DOI: 10.1088/0957-4484/20/27/275102
|View full text |Cite
|
Sign up to set email alerts
|

A mesoporous silica nanosphere-based drug delivery system using an electrically conducting polymer

Abstract: In this study, a mesoporous silica nanoparticle (MSN)-based nerve growth factor (NGF) delivery system has been successfully embedded within an electroactive polypyrrol (Ppy). The spherical particles with approximately 100 nm diameter possess a large surface-to-volume ratio for the entrapment of NGF into the pores of MSNs while retaining their bioactivity. Direct incorporation of MSN-NGF within Ppy was achieved during electrochemical polymerization. The loading amount and release profile of NGF from the composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 60 publications
2
53
0
Order By: Relevance
“…Cell culture testing using neuronal PC12 cells verified that NGF released from the films was active after electrical stimulation. However, the films produced a substantial amount of drug "leakage" in the absence of stimulation, although stimulation nearly doubled the final release quantity [318].…”
Section: Nanostructured Drug-releasing Cp Coatingsmentioning
confidence: 96%
See 1 more Smart Citation
“…Cell culture testing using neuronal PC12 cells verified that NGF released from the films was active after electrical stimulation. However, the films produced a substantial amount of drug "leakage" in the absence of stimulation, although stimulation nearly doubled the final release quantity [318].…”
Section: Nanostructured Drug-releasing Cp Coatingsmentioning
confidence: 96%
“…One method is to introduce nanodomains into the CP [318]. This can be accomplished by incorporating drug (NGF) into mesoporous silica nanoparticle reservoirs, which are then embedded within the CP along with the co-dopant PSS during electrochemical deposition resulting in a CP-based composite [318] (Fig.…”
Section: Nanostructured Drug-releasing Cp Coatingsmentioning
confidence: 99%
“…Investigators concluded that PPy promotes transport of SSA through PPA matrix, and its rate of release can be controlled by adjustment of the appropriate parameters. Cho et al [77] investigated mesoporous silica nanoparticles ( 100 nm in diameter) loaded with NGF and imbedded into PPy film. This system was able to control release of NGF, which induced specific cellular response in the PC-12 cells targeted by it.…”
Section: Release and Diffusionmentioning
confidence: 99%
“…However, electrochemical deposition using a solution composed of a biological entity and pyrrole monomers restricted homogeneous drug distribution throughout the PPy surface and interfered with electrochemical control of various parameters such as film thickness, loading concentration, and diffusion of the biomolecules of interest. In order to improve the performance of mesoporous CPCs, Cho's group proposed an alternative method [73]. As reservoirs of single or multiple substances, nanoparticles are capable of delivering highly concentrated chemical agents in a controlled-release manner [74][75][76][77][78].…”
Section: Othersmentioning
confidence: 99%